RELEVANSI DAN URGENSI TERHADAP PERATURAN DAERAH TENTANG PENYELENGGARAAN KETENAGAKERJAAN DI PROVINSI KEPULAUAN RIAU - Poti, Jamhur (Jurnal Ilmu Administrasi Negara (JUAN), 2018)
Employment problems in Indonesia have recently become very complex. Workers' demonstrations that occur as a result of prosecution of decent wages, working conditions, outsorcing, foreign workers, and the transfer of labor inspection authority from Regency / City to provinces and so on have disrupted the investment climate in Indonesia, especially in Riau Islands Province. This study, entitled The Relevance and Urgency of Regional Regulations concerning employment in the Riau Islands Province, aims to find out the relevance and urgency of a regulation, namely the Regional Scope of Employment in the Riau Islands Province. The method used in this study is the Forum Discussion Group (FGD) of various stakeholders. In order to make the implementation of labor in the Riau Islands Province a success, Riau Islands Provincial Government is expected to take a more active role through empowering internal resources through the APBD so that it can synergize with the central government program financed by the APBN. Synergy is expected to be realized through additional funding allocations to increase the capacity of the workforce in Riau Islands Province. The central government which has provided enough stimulation to the Regional Government must be followed by positive steps to add it through the APBD of the Riau Islands Province. So it is expected that in the future Riau Islands Province will have a competent, superior, and capable workforce in the global market.